Health behavior of Austrian tertiary students focusing on diet type linked to sports and exercise—first glimpse of results from the “sustainably healthy—from science 2 high school and university” study - Wirnitzer, Katharina C.; Motevalli, Mohamad; Cocca, Armando; Tanous, Derrick R.; Wirnitzer, Gerold; Wagner, Karl-Heinz; Schätzer, Manuel; Drenowatz, Clemens; Ruedl, Gerhard; Kirschner, Werner (Frontiers in Public Health, 2023)
Background: There is a strong association between lifestyle behavior and health status. While young adulthood is a critical period for adopting and stabilizing lifelong healthy behavior, university life is independently associated with psychological stressors that may further affect health and well-being. Objective: The present multidisciplinary study aimed to examine the health behavior of Austrian college and university students, differentiated based on diet types (vegan, vegetarian, omnivorous) and physical activity (PA) habits. Methods: Following a cross-sectional study design, a total number of 6,148 students (65.3% females; 66.1% bachelor students, 67.0% from urban areas; mean age: 24.8 y) from 52 Austrian college/universities participated in an online survey and provided data on sociodemographic characteristics, dietary patterns, PA habits, and other lifestyle behavior characteristics, including alcohol intake and smoking. Results: Across the total sample, 74.0% had a normal weight (BMI = 18.5-25.0 kg/m 2 ), while the prevalence of overweight/obesity (BMI ≥ 30.0 kg/m 2 ) was lower in females than males and more in rural than urban students (p < 0.01). The general prevalence of vegetarian and vegan diets was 22.8% and 6.0%, respectively, with a predominance of females, graduates, and urban students compared to their peers (p < 0.01). The majority of students (79.3%) had a regular engagement in sport/exercise, with a predominance of vegetarian or vegan students compared to omnivores (p < 0.01). Vegans and vegetarians had a lower alcohol intake (p < 0.01) but no differences in smoking habits (p > 0.05) compared to omnivores. Students engaging in sport/exercise had a lower smoking rate and higher intake of fruits, vegetables, and fluids compared to inactive students (p < 0.01). Conclusion: The present findings suggest that diet type and PA habits of college/university students have an impact on other health behaviors, highlighting the interconnected nature of lifestyle habits and health behavior.